Pengaruh Hukum Internasional Terhadap Pembentukan Hukum Nasional - Tahar, Abdul Muthalib (Jurnal Selat, 2015)
This full age agreement internationaling to constitute international law main source. teroritisâs ala international agreement can be differentiated of various aspect, of State amount aspect that makes agreement, differentiated international agreement as two, which is agreement bilateral (made by two States) and multilateral agreement / convention (made by is more than two states). In the presence international law (notably indentured international) have also been push Indonesia Government to make a law that substansinya loads indigenous rule a conventions that havenât at ratification, UUâs example human right Justice, substansinya loads indigenous rule Rome Statute 1998, eventually Indonesia Government havenât meratifikasi this Statute. Answer to about problem if international law having for to national jurisdictional forming, therefore bases fact description upon concluded that international law influentialing to formation national law. Keywords: International Law, National Law